Community-based learning management curriculum to enhance the local career skills on the development of fruit wine and fruit jam at Ban Wiang Haeng School under the Chiang Mai Primary Educational Service Area Office 3 - Pandon, Rattikan; Chumpoonuch, Sekchai; Wangcham, Sangwan (Journal of Humanities and Social Sciences, Rajapruk University, 2024)
The Objective of this research were to 1.explore the need for curriculum development to 2.establish, monitor, 3.test, and 4.evaluate the use of community-based learning management curriculum to enhance the local career skills on the development of fruit wine and fruit jam at Ban Wiang Haeng School under the Chiang Mai Primary Educational Service Area Office 3. The population consisted of 68 Pratom Suksa 6/1 students, parents, administrators, teachers, educational personnel, school committees, and local wisdom teachers. The tools used were curriculum development needs surveys, appropriateness assessments, curriculum composition consistency assessments, learning management plans, and curriculum satisfaction assessments. The data were analyzed by arithmetic averages, standard deviations, and content analysis. The results of the research revealed that the curriculum development needs of students, parents, and local wisdom teachers were at the highest level. The needs of administrators, teachers, educational personnel and the school committees were at a high level. The curriculum structure consisted of the curriculum destination,content structure/ learning time, learning standards, expected learning outcomes, learning content, learning management practices, course descriptions, media/learning resources,assessment and measurement, quality assessment, curriculum propriety, the overall average was at a high level, and the consistency of the curriculum, all issues were consistent. The results of the curriculum trial showed that the performance skills, career skills, and learning achievement were at the excellent level. The overall curriculum satisfaction assessment was at the highest level.